2010
DOI: 10.1016/j.jjcc.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effective regurgitant orifice area of mitral valvular regurgitation by multislice cardiac computed tomography

Abstract: MSCT provides reliable and good results for the evaluation of mitral regurgitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Although the sample size is very small, clinical outcomes shown in this study are consistent with APR severity classification by MDCT. Thus, we think the PARO area assessed by MDCT might be accurate [15], and is applicable for assessing prognostic impact of APR and for surgical planning such as closure device sizing.…”
Section: Paro Area By Mdctmentioning
confidence: 99%
“…Although the sample size is very small, clinical outcomes shown in this study are consistent with APR severity classification by MDCT. Thus, we think the PARO area assessed by MDCT might be accurate [15], and is applicable for assessing prognostic impact of APR and for surgical planning such as closure device sizing.…”
Section: Paro Area By Mdctmentioning
confidence: 99%
“…In terms of assessing MR severity by cardiac CT, two studies have demonstrated that CT-derived AROA correlates well with EROA measured by echocardiography (89,90). Quantitative RVol can be generated as the difference between the calculated stroke volume of the left and the right ventricle and has been shown to have a good correlation with the RVol obtained by CMR (91).…”
Section: Cardiac Ctmentioning
confidence: 99%
“…Interestingly, the tethering height ( 7.2 mm) of the TV seems to be associated with the recurrence of TR after TV annuloplasty [ 98 ]. Tricuspid anatomical regurgitation orifice area (AROA) can be measured with MPR by contouring the tips of TV leaflets in systole in a similar way to mitral valve regurgitation [ 99 ]. The AROA was recently calculated using Dual Source CT in 60 patients with symptomatic TR and compared to TR severity and VCA assessed at TEE.…”
Section: Diagnostic Work-up Of Severe Tricuspid Regurgitationmentioning
confidence: 99%